Gender-Based Violence in Schools and Girls' Education: Experimental Evidence from Mozambique - Sofia Amaral; Aixa Garcia-Ramos; Selim Gulesci; Sarita Oré; Alejandra Ramos; Maria Micaela Sviatschi (CESifo GmbH, 2024)
Gender-based violence (GBV) at schools is a pervasive problem that affects millions of adolescent girls worldwide. In partnership with the Ministry of Education in Mozambique, we developed an intervention to increase the capacity of key school personnel to address GBV and to improve students' awareness as well as proactive behaviors. To understand the role of GBV on girls' education, we randomized not only exposure to the intervention but also whether the student component was targeted to girls only, boys only, or both. Our findings indicate a reduction in sexual violence by teachers and school staff against girls, regardless of the targeted gender group, providing evidence of the role of improving the capacity of key school personnel to deter perpetrators. Using administrative records, we also find that in schools where the intervention encouraged proactive behavior by girls, there was an increase in their school enrollment, largely due to an increased propensity for GBV reporting by victims. Our findings suggest that effectively mitigating violence to improve girls' schooling requires a dual approach: deterring potential perpetrators and fostering a proactive stance among victims, such as increased reporting.
Keywords: O12; J16; I25; 330; gender-based violence; schooling